Living with secularism : the destiny of India's Muslims - Hasan, Mushirul (New Delhi : Manohar Publishers & Distributors : Distributed in South Asia by Foundation Books, 2007)
Contributed articles.
Sequel to: Will secular India survive?
Includes bibliographical references and index.
Keywords: MUSLIMS -- INDIA; HINDUTVA; SECULARISM -- INDIA; INDIA. -- ETHNIC RELATIONS